Perancangan Mainan "Odong-Odong" Sebagai Media Edukasi Tradisi Lokaluntuk Anak Usia 1-5 Tahun - Zarkasi, Much. Sofwan (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2012)
This article is a summary of the research that has been conducted by the author, titled â€œDesigning Toysâ€ Odong-odong â€œAs Media Education Local Traiding For Children Aged 1-5 Yearsâ€. this study is to reintroduce the children intheir world, which according to the present writer has been captured by the electronic mass media capitalists. Media odong-odong toys are usually only as a medium of entertainment media modified as local tradition based art education game,expected results of this designs is able to inspire people to develop and be differentiation products are much in demand by the children, which will indirectly increase the interest odong0odong to play, and also increase income enterpreneurs and artisans odong-odong. On the other side, the nature of entertainment media education is expected that children will be more familiar with local traditions and art imprint will continue until they later grow up, so they do not visually cultural identity tercaput of local cultural roots. This is important, because the issue is what actually became the main issue in the development of national identity.Keywords : odong-odong, media education, children, traditions.